O Estado e as políticas de qualificação profissional implantadas no sistema prisional - Miranda, Camila Maximiano (2008)
The range of criminality in modern society has led us to reflect about new social frameworks created as a result of globalization, of the growth and consolidation of neo liberalism, and of transformations in the work arena brought forth by new structuring of the productive forces. Such processes stem from the structural crises of capital, and highly contribute to intensifying the processes of instability of work augmenting the unemployment rate. Bearing this social panorama in mind, this paper aims to analyze the role of the State regarding the management of educational policies which aim to cut down on criminality by promoting professional qualification and re-training exconvicts so as to enable them to re-enter the job market. This paper focuses on the relationship between the public sphere and non-governmental organizations that are responsible for offering/ implementing re-training and crime prevention programs. I assume that the professional qualification policies implemented within the prison system do not contribute to the reduction of relapse, but reinforce the inclusion / exclusion paradox. This research brings to the fore voices and perceptions of both convicts as well as of those in charge of the State educational policies implemented in the prison systems. This study shows, through empirical evidence, the unsuitability of the convicts re-socialization processes, their uncertainties and the frailties of action plans to re-integrate ex-convicts in society and the job market, and also the State lack of interest in the prison system.